On the Uncleftability of Direct Object in Chinese - Luo, Cheng (Linguistica Atlantica, 1992)
While Keenan and Comrie's (1977) Accessibility Hierarchy (AH) theory has been considered applicable to syntactic processes other than relativization, apparent counterevidence is not lacking which poses a potential threat to the validity of the theory. For example, while in general Chinese cleft sentences obey the AH, the uncleftability of the direct object (DO) poses a problem for the AH. This study, however, shows that DO uncleftability in Chinese follows not from overgeneralization of the AH, but from a language-specific constraint on linear order between the contrastive focus marker, or more generally the quasi-verb, and the main verb in Chinese. Thus while the AH attains some measure of plausibility as a universal tendency, it nevertheless can interact with, and be negatively affected by, language-specific constraints.